STRATEGI PROMOSI BENGKEL BKRT GARAGE MELALUI KONTEN DIGITAL - Amalia, Ais; Yosep Soko Sago; Kristyana Dananti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This community service program aims to design and implement a digital content-based promotion strategy for BKRT Garage Workshop. Using a descriptive-qualitative approach, the program included observation, planning, content creation, and mentoring. Implementation was carried out on social media platforms such as Instagram, TikTok, and Facebook over a three-month period. The results showed a significant improvement in digital performance indicators: Instagram followers increased by approximately 96% (from 1,200 to 2,350), TikTok gained 1,500 new followers with an average of 10,000 views per video, and engagement (likes and comments) rose by 60%. Furthermore, customer visits to the workshop increased by around 30%, with 70% of new customers finding the workshop through social media. Content types such as before-after results and customer testimonials proved most effective. The program successfully enhanced the workshop’s visibility, audience engagement, and customer growth while building the partner's capacity to manage digital promotion independently. This model can be replicated by similar micro-enterprises in the automotive sector.